BS EN 2997-004. Aerospace series. Connectors, electrical, circular, coupled by threaded ring, fire-resistant or non fire-resistant, operating temperatures - 65 °C to 175 °C continuous, 200 °C continuous, 260 °C peak. Part 004. Jam-nut mounted receptacle - Product standard (28th April 2022) - British Standards Institution,
No abstract available